QUINT: Workflow for Quantification and Spatial Analysis of Features in Histological Images From Rodent Brain - Yates, Sharon C.; Groeneboom, Nicolaas E.; Coello, Christopher; Lichtenthaler, Stefan F.; Kuhn, Peer-Hendrik; Demuth, Hans-Ulrich; Hartlage-Rübsamen, Maike; Roßner, Steffen; Leergaard, Trygve; Kreshuk, Anna; Puchades, Maja A.; Bjaalie, Jan G. (Frontiers in Neuroinformatics, 2019)
Transgenic animal models are invaluable research tools for elucidating the pathways and mechanisms involved in the development of neurodegenerative diseases. Mechanistic clues can be revealed by applying labelling techniques such as immunohistochemistry or in situ hybridisation to brain tissue sections. Precision in both assigning anatomical location to the sections and quantifying labelled features is crucial for output validity, with either using a stereological approach or an image based feature extraction. However, both approaches are restricted by the need to manually delineate anatomical regions. To circumvent this limitation, we present the QUINT workflow for quantification and spatial analysis of labelling in series of rodent brain section images based on available 3D reference atlases. The workflow is semi-automated, combining three open source software that can be operated without scripting knowledge, making it accessible to most researchers. As an example, a brain region specific quantification of amyloid plaques across whole transgenic Tg2576 mouse brain series, immunohistochemically labelled for three amyloid related antigens is demonstrated. Firstly, the whole brain image series were registered to the Allen Mouse Brain Atlas to produce customised atlas maps adapted to match the cutting plan and proportions of the sections (QuickNII software). Secondly, the labelling was segmented from the original images by the Random Forest Algorithm for supervised classification (ilastik software). Finally, the segmented images and atlas maps were used to generate plaque quantifications for each region in the reference atlas (Nutil software). The method yielded comparable results to manual delineations and to the output of a stereological method. While the use case demonstrates the QUINT workflow for quantification of amyloid plaques only, the workflow is suited to all mouse or rat brain series with labelling that is visually distinct from the background, for example for the quantification of cells or labelled proteins.